Evaluating the potential for quantitative monitoring of in situ chemical oxidation of aqueous‐phase TCE using in‐phase and quadrature electrical conductivity. Issue 7 (14th July 2015) - Hort, R. D.; Revil, A.; Munakata‐Marr, J.; Mao, D.
Abstract: Electrical resistivity measurements can potentially be used to remotely monitor fate and transport of ionic oxidants such as permanganate ( MnO 4 − ) during in situ chemical oxidation (ISCO) of contaminants like trichloroethene (TCE). Time‐lapse two‐dimensional bulk conductivity and induced polarization surveys conducted during a sand tank ISCO simulation demonstrated that MnO 4 − plume movement could be monitored in a qualitative manner using bulk conductivity tomograms, although chargeability was below sensitivity limits. We also examined changes to in‐phase and quadrature electrical conductivity resulting from ion injection, MnO2 and Cl − production, and pH change during TCE and humate oxidation by MnO 4 − in homogeneous aqueous solutions and saturated porous media samples. Data from the homogeneous samples demonstrated that inversion of the sand tank resistivity data using a common Tikhonov regularization approach was insufficient to recover an accurate conductivity distribution within the tank. While changes to in‐phase conductivity could be successfully modeled, quadrature conductivity values could not be directly related to TCE oxidation product or MnO 4 − concentrations at frequencies consistent with field induced polarization surveys, limiting the utility of quadrature conductivity for monitoring ISCO. Key Points: 2‐D conductivity tomograms can qualitatively track permanganate movement Tikhonov regularization alone cannot produce accurate conductivity distributions In situ chemical oxidation modeling may improve inversions, allowing quantitative use of tomograms